English Language Variation of Tourist Guide: A Case Study of Indonesian Context - Fhadli Noer; Zul Astri; Nurul Hidjrah Hairuddin (SELTICS, 2021)
Individuals frequently speak English differently depending on their native language or the society they live in. A primary goal of our research is to learn more about the unique linguistic characteristics of the Indonesian people. This study aims to discover the language variation of English used by Indonesian tourist guides. Researchers used library and field research to perform the analysis. The researcher gathered data by recording, transcribing, and categorizing it in three separate processes. Furthermore, the researchers utilized a descriptive qualitative method to examine the usual linguistic features of English used by the tour guide. According to the findings of this study, the code choice of the three tour guides is relatively comparable. They used some particular lexical, namely actually, so, this is I and ‘and then’ In addition, they perform code-switching and code-mixing. Keywords: English, Language Variation, Tourist, Guide, Indonesia